2011
DOI: 10.1177/1049732311405798
|View full text |Cite
|
Sign up to set email alerts
|

The Emotional Journey of Women Experiencing a Breast Abnormality

Abstract: Using grounded theory, a multidisciplinary study team compared the narratives of 30 women who had recently experienced a breast cancer scare. Even though 10 women received a benign diagnosis, all women reported a difficult time prediagnosis, characterized by an array of emotions and contemplation of the meaning of life. Diagnosis separated the two groups with emotional relief dominant for the benign group and intensification of emotions for the cancer group. For those diagnosed with cancer, three factors contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 33 publications
1
25
0
1
Order By: Relevance
“…; Blow et al . ; Banning & Tanzeem ). Breast cancer and its treatments can lead to numerous negative emotional consequences such as disbelief, despair, fear, feeling out of control and self‐blame (Shaha et al .…”
Section: Introductionmentioning
confidence: 99%
“…; Blow et al . ; Banning & Tanzeem ). Breast cancer and its treatments can lead to numerous negative emotional consequences such as disbelief, despair, fear, feeling out of control and self‐blame (Shaha et al .…”
Section: Introductionmentioning
confidence: 99%
“…After their event, faith became part of their viewpoint on why change was important. This perspective of purpose was also identified in a recent study by Blow et al (2011) in which they identified similar findings for women who had been diagnosed with breast cancer. The women of the present study indicated that their faith and belief was a source of strength and encouragement to continue.…”
Section: Faith and Personal Responsibilitymentioning
confidence: 59%
“…Although we do not have sufficient data to investigate biological association of these two factors with each cause of mortality, one reason for increased risk of non-cancer mortality could be anxiety caused by discovery of a breast abnormality [24]. Women who experience the discovery will be coping with fears about the future and dealing with emotional ups and downs [24]. …”
Section: Discussionmentioning
confidence: 99%